STRATEGY TO RAISE AWARENESS OF INFORMAL SECTOR WORKERS TOWARDS PARTICIPATION IN THE BPJS EMPLOYMENT SOCIAL SECURITY PROGRAM: A DESCRIPTIVE ANALYSIS OF THE WELERI MARKET, KENDAL DISTRICT, CENTRAL JAVA PROVINCE: - Rahayu, Dina Setya; Ocktilia, Helly (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
Awareness-building strategies are essential to increase understanding and participation of informal sector workers in social protection programs. This study aims to describe the development of an awareness-building model for informal workers in Weleri Market in relation to their participation in the Employment Injury Insurance (JKK) and Death Insurance (JKM) programs of BPJS Ketenagakerjaan. Using a qualitative descriptive method, data were collected through in-depth interviews, observations, and document reviews. Informants consisted of representatives from BPJS Ketenagakerjaan, the Manpower Office, the Market Management Unit (UPTD), and Weleri Market traders. The findings indicate that existing outreach efforts such as direct socialization, printed media, social media, and the JMO application have not been implemented consistently and are not yet fully accessible or understood by informal workers. Participation is shaped by internal factors (self-awareness, understanding of benefits, family support) and external factors (service access, age, digital literacy). Based on these findings, the study formulates the JEMPOL TANGGUH model (Jaminan Sosial Pekerja Lokal Tanggap, Unggul, dan Humanis) as a community-based strategy to strengthen workers’ awareness and participation. This model emphasizes structured, continuous, and contextual interventions through multi-stakeholder involvement, aiming to enhance information delivery, improve worker capacity, and build a more inclusive and responsive social protection ecosystem in traditional market settings.